Bioethics teaching. generation and implementation of courses in Regional University of O'Higgins (Chile) - Rueda-Castro, Laura (2023)
The training team in bioethics of health careers at the Regional State University of O'Higgins, Chile (UOH), presents the systematization of what has been five years between the design and implementation of the programs for bioethics courses, according to the local needs investigated. In 2018, qualitative research was carried out taking the entry cohort of that year, whose purpose was to identify the training needs in bioethics of the local community for the redesign of the courses. The academics courses imparted by 3 successive years, change at the first semester of 2020, due to the sanitary crisis, adjusting to an online modality. The reflection reviews whether participation, collective production and questioning are preserved as an achievement of the educational purposes in the courses taught in person. On the occasion of the contingency and given the results obtained, the in-person program and design is modified to a virtual one, since the requirements of the students have been known. From the teaching experience systematized and presented, it is concluded that even in the face of the health contingency situation, the educational objectives for training in bioethics are achieved; that is to say that the students achieve the acquisition of an autonomous moral judgment for the decisions of their professional practice, the understanding of science, technology and the social problems that they have to face; managing the deliberative method of ethics in the field of health.